2022
DOI: 10.1021/jacs.2c09285
|View full text |Cite
|
Sign up to set email alerts
|

Photomechanical Motions in Organoboron-Based Phosphorescent Molecular Crystals Driven by a Crystal-State [2 + 2] Cycloaddition Reaction

Abstract: Photoluminescent molecular crystals integrated with the ability to transform light energy into macroscopic mechanical motions are a promising choice of materials for both actuating and photonic devices. However, such dynamic photomechanical effects, based on molecular organoboron compounds as well as phosphorescent crystalline materials, are not yet known. Here we present an intriguing example of photomechanical molecular single crystals of a newly synthesized organoboron containing Lewis acid−base molecular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 61 publications
(93 reference statements)
1
33
0
Order By: Relevance
“…[26] In order to develop devices that can perform photomechanical movements on a macroscopic level, the most important issue is to find or design suitable compounds that can undergo photoreactions such as photoisomerization, photocycloaddition. [27] To date, only a few kinds of organic compounds such as azobenzenes, [28][29][30] anthracenes, [31,32] diarylethenes, [33][34][35][36] furylfulgides [37] and spiropyran [38] are known to trigger photoactuation behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] In order to develop devices that can perform photomechanical movements on a macroscopic level, the most important issue is to find or design suitable compounds that can undergo photoreactions such as photoisomerization, photocycloaddition. [27] To date, only a few kinds of organic compounds such as azobenzenes, [28][29][30] anthracenes, [31,32] diarylethenes, [33][34][35][36] furylfulgides [37] and spiropyran [38] are known to trigger photoactuation behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the microscopic atomic displacements and the strong structural resistance inside the materials, it is still a great challenge to achieve the direct photomechanical motions of photoresponsive materials or devices on a macroscopic scale [26] . In order to develop devices that can perform photomechanical movements on a macroscopic level, the most important issue is to find or design suitable compounds that can undergo photoreactions such as photoisomerization, photocycloaddition [27] . To date, only a few kinds of organic compounds such as azobenzenes, [28–30] anthracenes, [31, 32] diarylethenes, [33–36] furylfulgides [37] and spiropyran [38] are known to trigger photoactuation behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…20,25 Accordingly, the template-assisted method has been employed for the prearrangement of styrylpyridine units in crystals so as to make the packing meet Schmidt's criteria. 26,27 Vittal and Rath presented the photosalient behavior of the crystal based on the complexes where the distorted octahedral Pb(II) center is coordinated to the N atom in styrylpyridine derivatives and the strain is generated during the photo-induced [2 + 2] cycloaddition reaction. 28,29 MacGillivray et al reported the supramolecular alignment between resorcinol and styrylpyridine via multiple H-bonds of O−H•••N so as to realize the photochemical reaction-powered mechanical response of the crystals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As for the olefin-based molecular crystals, [2 + 2] cycloaddition between adjacent CC double bonds would trigger the macroscopic mechanical motions. Although styrylpyridine is one of the widely studied building blocks in photomechanical systems, , the distance between adjacent CC double bonds was often greater than 4.2 Å in crystals. , Accordingly, the template-assisted method has been employed for the prearrangement of styrylpyridine units in crystals so as to make the packing meet Schmidt’s criteria. , Vittal and Rath presented the photosalient behavior of the crystal based on the complexes where the distorted octahedral Pb­(II) center is coordinated to the N atom in styrylpyridine derivatives and the strain is generated during the photo-induced [2 + 2] cycloaddition reaction. , MacGillivray et al reported the supramolecular alignment between resorcinol and styrylpyridine via multiple H-bonds of O–H···N so as to realize the photochemical reaction-powered mechanical response of the crystals . Besides, much effort is also made to optimize the olefin geometry, such as cocrystal engineering.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] When exposed to light, photomechanical crystals may exhibit various macroscopic mechanical effects such as bending, twisting, cracking, expanding, splitting, and jumping due to their molecular-level transformation in terms of isomerization, [11][12][13] cyclization, [2a, 14, 15] and various topochemical reactions. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] However, macroscopic photodynamic motions of single crystals mostly require activation with damaging and high energy UV light which limits their practical applications. [10,23,29] In this context, the photomechanical bending with solid-state reactions in a few molecular crystals under visible light has previously been explored.…”
Section: Introductionmentioning
confidence: 99%